Gambaran Motivasi Belajar pada Siswa Pengguna Smartphone di SMP Negeri 4 Garut - Sri Yekti Widadi; Inge Ajeng Pramudita (Jurnal Keperawatan Silampari, 2018)
The purpose of this research is to find out the description of learning motivation in smartphone users in SMP Negeri 4 Garut. The research method in this research is to use a descriptive research method. The results of the study half of the students (50.6%) rarely use smartphones and almost half the students (41.6%) have enough motivation to learn in SMP Negeri 4 Garut. Conclusion, Students who rarely use smartphones have sufficient learning motivation and students who often use smartphones have less learning motivation. Keywords: Learning Motivation, Smartphone Use